DEVELOPMENT OF A MODULE BASED ON RIAU LOCAL WISDOM ON NORMS IN MY LIFE MATERIAL FOR GRADE V ELEMENTARY SCHOOL STUDENTS: PENGEMBANGAN MODUL BERBASIS KEARIFAN LOKAL RIAU PADA MATERI NORMA DALAM KEHIDUPANKU UNTUK SISWA KELAS V SD - Gusrika Fauza Rofah; Zaka Hadikusuma Ramadan (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This research aims to develop a learning module based on Riau local wisdom on the material